The Effect Of Earning Management On Earning Response On Properties & Real Estate Sub-Sector Companies Listed On The Indonesia Stock Exchange In 2019-2023 - Vebriance Stefania Manek (Universitas Trunodjoyo Madura, 2025)
This research aims to analyze the effect of earnings management on earning response among property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2023. Earnings management is measured using two approaches, namely income smoothing and earnings quality, while earning response is measured using the stock return indicator. This research uses a quantitative approach with secondary data obtained from the company's financial statements. The sample is determined using the purposive sampling method which allows for the identification of a number of companies that meet the research criteria. The results indicate that income smoothing has a significant positive impact on earning response, suggesting that the market responds positively to the income smoothing practices carried out by companies. On the other hand, the quality of profits shows a negative impact on earning response, indicating that the lower the quality of profits generated, the more negative the earning response to the company's financial information. These findings imply that investors need to be more diligent in evaluating the profit management practices and quality of accounting information provided by the company before making investment decisions.